2022
DOI: 10.3389/fgene.2022.836431
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mutation of Transferrin Receptor 2 in a Chinese Pedigree With Type 3 Hemochromatosis: A Case Report

Abstract: Type 3 hereditary hemochromatosis (HH) is a rare form of HH characterized by genetic mutation in the TFR2 gene. Clinical features reported in patients with type 3 HH include abnormal liver function, liver fibrosis, cirrhosis, diabetes, hypogonadism, cardiomyopathy, and skin pigmentation. Since its original description in 2000, 33 pathogenic TFR2 mutations associated with HH have been described until now. Here, we first reported a Chinese pedigree of TFR2-related hemochromatosis with a novel compound heterozygo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…(Tyr320*); and SLC40A1 p. (Cys326Phe). [11][12][13][14] In a multi-center study, we have recently identified a series of variants in hemochromatosis in non-HFE genes, including HJV p.(His104Arg) and p.(Val274Met); TFR2 p.(Ala302Glu) and p.(Leu745Arg); and SLC40A1 p.(Tyr333His). 15,16 However, there are still many unexplained cases of primary iron overload with no causative variant in known hemochromatosis-related genes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Tyr320*); and SLC40A1 p. (Cys326Phe). [11][12][13][14] In a multi-center study, we have recently identified a series of variants in hemochromatosis in non-HFE genes, including HJV p.(His104Arg) and p.(Val274Met); TFR2 p.(Ala302Glu) and p.(Leu745Arg); and SLC40A1 p.(Tyr333His). 15,16 However, there are still many unexplained cases of primary iron overload with no causative variant in known hemochromatosis-related genes.…”
Section: Introductionmentioning
confidence: 99%
“…(Gly430Arg) and p.(Gly430Arg)/p. (Tyr320*); and SLC40A1 p. (Cys326Phe) 11–14 . In a multi‐center study, we have recently identified a series of variants in hemochromatosis in non‐ HFE genes, including HJV p.(His104Arg) and p.(Val274Met); TFR2 p.(Ala302Glu) and p.(Leu745Arg); and SLC40A1 p.(Tyr333His) 15,16 .…”
Section: Introductionmentioning
confidence: 99%